Elementary School Student Response to Children's Storybooks with Emotional Literacy - Seni Apriliya; Erwin Rahayu Saputra; Cyntia C (Indonesian Journal of Primary Education, 2022)
This research is motivated by the urgency of emotional literacy teaching materials for elementary school students. One of the efforts that can be done is to cultivate emotional literacy through fictional texts or children's literature in the form of children's story books. There are a number of studies on children's stories containing emotional literacy. However, the response of students to children's story books containing emotional literacy is still limited. Therefore, this  purpose study aims to describe the responses of elementary school students to children's story books containing emotional literacy. This research is part of the Educational Design Research (EDR) research model. Data collection techniques used, namely distributing questionnaires to 13 students and studying literature. The results showed that the students' responses to children's story books containing emotional literacy were included in the good category because they met five indicators of reading interest, namely meeting the reading needs of children's stories containing emotional literacy; according to the interests of students; feelings of pleasure that arise in students after reading story books containing emotional literacy; acknowledge interest in reading children's stories containing emotional literacy; and the spirit of reading and following up the values obtained from reading into life. Thus, it can be concluded that children's story books containing emotional literacy were responded well by students while providing a good emotional literacy experience. The implication is that it requires exploration of response-oriented strategies and techniques in learning or non-learning that empowers children's story books with emotional literacy